Fragmentation of presidential elections and governability crises in Latin America: a curvilinear relationship?. Issue 7 (3rd October 2018) - Kouba, Karel; Došek, Tomáš
ABSTRACT: Part of the literature views high numbers of presidential candidates as a threat to political stability in presidential democracies. A contradictory model proposes that an overconcentration of the presidential party system is problematic. Both models are hard to reconcile. We approach this puzzle by arguing that the relationship between the level of presidential election fragmentation and governability crises is curvilinear: both very low and very high effective numbers of presidential candidates increase the risk of governability crisis. We test this theoretical claim with ordered logit models drawing on a sample of 108 presidencies in Latin America between 1978 and 2013 and using an ordinal index of the intensity of crisis as the dependent variable. We explore the operation of the theorized causal mechanisms through case studies and argue that they are different at both extremes, high and low levels of fragmentation. Finally, we formulate implications for the design of presidential electoral rules drawing on the debate contrasting runoff and plurality rules.